Regulation of Blood-Boosting Supplements for Anemia in Pregnant Women: Literature Review - Eni Widhiyaastuti; Arih Diyaning Intiasari; Suratman (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Introduction: The number of pregnant women who suffer from anemia is 57.1% in Africa, 48.2% in Asia, 25.% in Europe, and 24.1 % in the US respectively. The 2021 Riskesdas shows that 78% of pregnant women experience anemia, up from 48.9% in 2019. Method: This research is a literature study using the PRISMA diagram approach, with article searches using the research databases Pubmed, Science Direct, Google Scholar, Sage Journal and Scopus from 2018-2024. The author formulated PICO to direct clinical searches, with the keywords